Acute and Chronic Ecotoxicity of Daphnia magna Exposed to Ash Leachate from the Cotopaxi Volcano, Ecuador - Pinos-Velez, V. P.; Araujo, G. S. [UNESP]; Echeverria-Paredes, P.; Abril, M.; Acosta, S.; Cipriani-Ávila, I.; Moulatlet, G. M.; Capparelli, M. V. (Springer Nature, 2024)
Ecuador’s wetlands and aquatic ecosystems are chronically exposed to ash contamination due to the frequent volcanoes’ eruptions in the country. Still, the short and long-term effects of ash contamination on the aquatic biota are not well understood. We used ashes released by the Cotopaxi volcano in 2016 to investigate their acute and chronic effects in Daphna magna. We calculated the half maximal effective concentration (EC50) after 2 and 21 days of exposure, the non-observed effect concentration (NOEC), and the lowest observed effect concentration (LOEC) on offspring production. We also analyzed the metal concentration present in the ashes. The EC50 values at 2 and 21 days were found at 80% and 5% ash leachate concentrations, respectively. After 21 days of exposure, high mortality and low neonatal production were observed in all leachate concentrations (NOEC was at 15%, and LOEC was at 20% leachate concentration). Our results suggest that the ashes from the Cotopaxi volcano can cause acute and chronic toxicity to aquatic life and should be classified as hazardous waste, depending on the dose. There is an urgent need for further studies that assess toxicity caused by the intense volcanic activity in Ecuador.
Keywords: EC50; LOEC; NOEC; Potentially toxic elements; Wetlands